Elevation Correlates With Significant Changes in Relative Abundance in Hummingbird Fecal Microbiota, but Composition Changes Little - Herder, Elizabeth A.; Spence, Austin R.; Tingley, Morgan W.; Hird, Sarah M. (Frontiers in Ecology and Evolution, 2021)
The microbial communities living on and in vertebrate hosts have myriad effects on their hosts, potentially including fitness and speciation. Microbiomes are influenced by both intrinsic (from the host) and extrinsic (from the environment) factors, but the relative contributions of each are unknown for most non-model species. Abiotic environmental factors can influence the microbiome directly but it is less clear how abiotic gradients shape microbiome communities in the wild. Here, we captured eight wild Anna’s hummingbirds from three different elevations along their elevational distribution in California and moved them directly to a middle (“Within Range”) elevation. After some time at this elevation, the birds were moved in captivity to an “Above Range '' elevation, and two birds were later moved back to the Within Range elevation. Fecal and food samples were collected longitudinally and the V4 region of the 16S rRNA gene analyzed. The most abundant phyla in all samples were Fusobacteria, Firmicutes, Actinobacteria, and Proteobacteria, Individual Bird ID explained the greatest amount of microbiome variation at 27.5%, signifying some amount of stability in the Anna’s hummingbird fecal microbiome. Sample elevation explained 19.6% (p = 0.001) of the variation using weighted UniFrac, but only 2.0% (p = 0.047) using unweighted UniFrac, implying a change in abundance of bacterial lineages in the microbiome but not in the presence or absence of the microbes. Additionally, Fusobacteria were 7.0x more abundant in the Above Range elevation samples while Firmicutes were 0.3x lower. A thorough understanding of how the environment can shape the microbiome may assist in conservation efforts and a general understanding of host-microbiome relationships in an era of rapid and global environmental change.